Patient Confidentiality and Ethical Behaviour as a Professional Commitment in Dentistry: A Case Study in a Genetic Disorder - Anderson, Greg; Sadighpour, Leyla (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2020)
A professional commitment to patient confidentiality may sometimes contradict other principles of bioethics. Decision-making for doctors and their team can be challenging amidst such conflicting principles, and despite the practitioner’s best intentions, withholding information can result in potential consequences such as harm to others.